Early developmental outcomes in children following convulsive status epilepticus: A longitudinal study. (8th April 2013) - Martinos, Marina M.; Yoong, Michael; Patil, Shekhar; Chong, Wui K.; Mardari, Rodica; Chin, Richard F. M.; Neville, Brian G. R.; de Haan, Michelle; Scott, Rod C.
Summary Purpose Convulsive status epilepticus (CSE) is the most common pediatric neurologic emergency and is often associated with unfavorable neurodevelopmental outcomes. The early developmental trajectory of children following CSE has not been previously investigated, leaving a gap in our understanding of how these adverse long‐term outcomes emerge. Methods We prospectively recruited children aged between 1 and 42 months from a predefined geographic region of North London who had at least one episode of CSE and classified them as prolonged febrile seizures (PFS) or nonfebrile CSE. Neuropsychological and imaging investigations were conducted within 6 weeks of CSE (baseline) and were repeated a year later (follow‐up). Neurodevelopment was assessed using the Bayley Scales of Infant Development III and compared to normally developing children. Predictors of neurodevelopmental scores at baseline and follow‐up were investigated using regression analyses. Key Findings Of the 54 children that underwent investigations a mean of 38 days following CSE, 27 had PFS (mean age 18.4 months) and 27 had nonfebrile CSE (mean age 15.5 months). In addition, 17 healthy controls were assessed (mean age 20.49 months). Children with nonfebrile CSE had a worse developmental outcome than children with PFS (p < 0.002), despite there being no differences in seizure characteristics. In contrast to expectations, the PFS group had a worse developmental outcome than controls (p = 0.002). There were no significant differences in performance from baseline to 1‐year follow‐up for the 70.4% of children who provided data. Seizure characteristics were not shown to be significant predictors of performance. Significance CSE is associated with developmental impairments within 6 weeks of the acute event that continue to be present a year onward. This is also true of PFS cases that under‐perform relative to controls despite mean scores within the clinically normal range. The absence of a change in performance from baseline to follow‐up as well as the lack of a relationship between seizure characteristics and developmental outcomes supports the notion that premorbid abilities may be overshadowing any direct effects of CSE itself on outcome.